The aspects of the islamization on the territory of Bosnia in the 15th century and in the first half of the 16th century - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 2011)
The article concerns the process of Islamization in Bosnia after the Ottoman conquest during the fifteenth and the first half of the sixteenth century. The author analyzes the social, political, and religious conditions behind the adoption of Islam by the Bosnian population and presents various interpretations of this phenomenon in historiography. The aim of the article is to provide a comprehensive explanation of the Islamization process and to assess the factors influencing its dynamics. The author employs an analysis of historical sources and a critique of the relevant literature. The study demonstrates that the Islamization of Bosnia was a gradual and multi-causal process connected both with political transformations following the Ottoman conquest and with the earlier religious specificity of the country, where the Bosnian Church held a strong position. The author also emphasizes the importance of cooperation between part of the Bosnian elites and the Ottomans, as well as the strategic role of areas such as Vrhbosna. The article concludes that Islamization was not solely the result of Ottoman coercion, but rather the outcome of complex social and political processes taking place in Bosnia after its conquest by the Turks.